A review of experimental and numerical analysis on laser beam machining of composites and thermoplastics - Kaveh, Moghadasi; Khairul Fikri, Tamrin; Fahizan, Mahmud; Marzie Hatef, Jali (NUST Journal of Engineering Sciences (NJES), 2023)
Material cutting is a crucial process owing to its strategic value in producing items such as aircraft, ships, automobiles, biomedical components, etc. Laser beam cutting is among the efficient techniques for creating complicated geometries with rigorous design criteria. This article discusses the experimental study of the laser -cutting process and the effect of laser -cutting parameters on composites and thermoplastics. Several numerical modeling and different optimization approaches employed by various researchers are also reviewed in this article.